2002
DOI: 10.1002/jms.330
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of grafted poly(ethylene glycol)‐silanes on silicon by time‐of‐flight secondary ion mass spectrometry

Abstract: Silicon grafted monodisperse poly(ethylene glycol) (PEG) silanes with various PEG chain lengths and mixtures of these were systematically analyzed with static time-of-flight secondary ion mass spectrometry (TOF-SIMS). The mass spectra show differences in the various relative signal intensities, an observation that was used to elucidate important aspects of the grafting process. The relationship between PEG-silane fragment ion abundances and Si(+) ion abundances were used to (i) qualitatively describe layer thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…The wetting characteristics of PDMS ox and PDMS ox grafted with EO 18 increasingly approach those of PDMS ox treated with EO 〈 70 〉 in four steps when the number of anchoring groups increases from none to two. It is difficult to predict how the MW of the EO polymers and the number of silane anchoring groups influence the composition and hydrophilicity of the resulting layer: the conformation (coiled vs stretched) of the PEO in solution, the number and accessibility of the anchoring groups, the density and lifetime of adsorption sites on PDMS ox , and chemical yields when successive steps are employed to graft PEO all convolve to define the final structure of the air−stamp interface. We found it impractical to vary too many of these parameters and difficult to characterize the resulting interface in a direct manner. Therefore, we performed several series of ellipsometry-based experiments on grafting PEO to the native oxide of a Si wafer that was freshly cleaned using an O 2 -based plasma.…”
Section: Resultsmentioning
confidence: 99%
“…The wetting characteristics of PDMS ox and PDMS ox grafted with EO 18 increasingly approach those of PDMS ox treated with EO 〈 70 〉 in four steps when the number of anchoring groups increases from none to two. It is difficult to predict how the MW of the EO polymers and the number of silane anchoring groups influence the composition and hydrophilicity of the resulting layer: the conformation (coiled vs stretched) of the PEO in solution, the number and accessibility of the anchoring groups, the density and lifetime of adsorption sites on PDMS ox , and chemical yields when successive steps are employed to graft PEO all convolve to define the final structure of the air−stamp interface. We found it impractical to vary too many of these parameters and difficult to characterize the resulting interface in a direct manner. Therefore, we performed several series of ellipsometry-based experiments on grafting PEO to the native oxide of a Si wafer that was freshly cleaned using an O 2 -based plasma.…”
Section: Resultsmentioning
confidence: 99%
“…Then silica particles were dried in a stream of nitrogen and stored in a nitrogen environment until further usage. The surface modification of silica particles was performed via a silanization process [54,55]. During the silanization reaction, ethoxysilane moieties available in the mPEG silane (Figure 1) are detached with the coupling reaction and Si-O-Si bonds between Si atoms of mPEG and silica surface are formed [54,56].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, tremendous research efforts have been devoted to obtain quantitative information on surface functional groups by combining different techniques. [23] For example, Fischer et al found the relationship between fluorescence and XPS signals, which allows a direct correlation between an analysis of fluorescence and quantification of XPS. [20] However, it met significant challenges to quantify the grafting density of silane without nitrogen element such as silanes with aliphatic chains.…”
Section: Introductionmentioning
confidence: 99%